Acquisition of Physics in Secondary School in Context of Bionics - Poplavskis, Jānis; Dzerviniks, Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In the last few years, a lot of attention has been paid to science as a subject, including improvements of physics curriculum and developments in teaching process in order to boost students’ interest in this subject, and improve the quality of knowledge. One of potential solutions that are being offered is to include elements of bionics in physics curriculum, to show the transfer of processes of nature into everyday life and technology. A short introduction in bionics is provided in the research. In order to realise this plan, information has to be gathered – what is the students’ and teachers’ understanding of bionics, it’s role and possibilities in the learning process. During the research middle-school students and teachers have been surveyed, about questions and processes, that are connected to bionics. Books that are included in the physics curriculum have also been researched, in order to detect the existence of bionics’ elements and their usage.